2013
DOI: 10.1021/jp309368q
|View full text |Cite
|
Sign up to set email alerts
|

Radiative and Nonradiative Lifetime Engineering of Quantum Dots in Multiple Solvents by Surface Atom Stoichiometry and Ligands

Abstract: CdTe quantum dots have unique characteristics that are promising for applications in photoluminescence, photovoltaics or optoelectronics. However, wide variations of the reported quantum yields exist and the influence of ligand-surface interactions that are expected to control the excited state relaxation processes remains unknown. It is important to thoroughly understand the fundamental principles underlying these relaxation processes to tailor the QDs properties to their application. Here, we systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 58 publications
5
82
0
Order By: Relevance
“…The nonradiative rate increase originates from the increase in the number mid-gap hole states. Similar studies have found comparable patterns in CdTe nanoparticles with increasing telluride concentration on surfaces 19 , where hole traps and less passivated telluride surfaces contribute to increased nonradiative rates. Further, selenium rich surfaces on CdSe cores also produce insufficiently passivated particle surfaces 54 and comparable changes in fluorescent lifetimes 21 …”
Section: Effect Of Surface Composition On Fluorescence Dynamicssupporting
confidence: 72%
See 1 more Smart Citation
“…The nonradiative rate increase originates from the increase in the number mid-gap hole states. Similar studies have found comparable patterns in CdTe nanoparticles with increasing telluride concentration on surfaces 19 , where hole traps and less passivated telluride surfaces contribute to increased nonradiative rates. Further, selenium rich surfaces on CdSe cores also produce insufficiently passivated particle surfaces 54 and comparable changes in fluorescent lifetimes 21 …”
Section: Effect Of Surface Composition On Fluorescence Dynamicssupporting
confidence: 72%
“…Due to their large surface to volume ratio, the surface of QDs has been historically recognized as integral in influencing the optical properties of colloidal QDs 6,[18][19][20][21][22][23][24][25][26] . For example, early synthetic breakthroughs that produced highly-fluorescent QDs were enabled, in part, by the discovery that phosphine ligands provided effective passivation of dangling bonds at the nanoparticle surface 27 .…”
Section: Introductionmentioning
confidence: 99%
“…22 Briefly, ODA-QDs were precipitated from toluene by the addition of acetone (VWR), centrifuged at 1900g (4000rpm on a Clinical 50 centrifuge, VWR) and the supernatant discarded. DHLA or MPA was dissolved in methanol, and the solution adjusted to pH 10 by the addition of tetramethylammonium hydroxide pentahydrate (Alfa Aesar).…”
mentioning
confidence: 99%
“…The surface atom ratio may indeed result in different affinities to ligand functional groups, as previously shown for core-only CdTe. 22 Quantifying this ratio for core-shell QDs is more difficult due to the lack of techniques that probe surface atoms without interference from internal atoms, but will lead to a more thorough understanding of non-specific binding mechanisms, and will be the focus of future studies.…”
mentioning
confidence: 99%
“…5,22,27 However, such ligand exchange can induce numerous surface states acting as hole traps. 22,28 Indeed, a drastic decrease in the PL QY of the core QDs was observed after ligand exchange due to the quenching by the surface hole traps. 16 However, the PL QY decreased significantly less if the shell is coated well around the core (see the inset in Fig.…”
mentioning
confidence: 99%